2016
DOI: 10.1093/jrr/rrw040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined radiofrequency field exposure on amyloid-beta–induced cytotoxicity in HT22 mouse hippocampal neurones

Abstract: Alzheimer's disease (AD) is the most common progressive and irreversible neurodegenerative disease and it is caused by neuronal death in the brain. Recent studies have shown that non-ionizing radiofrequency (RF) radiation has some beneficial cognitive effects in animal models of AD. In this study, we examined the effect of combined RF radiation on amyloid-beta (Aβ)–induced cytotoxicity in HT22 rat hippocampal neurons. Treatment with Aβ suppressed HT22 cell proliferation in a concentration-dependent manner. RF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Similarly, no signs of inflammation, such as more iNOS or NO formation, were found in astrocytes after exposure to 1.8 GHz RF-EMF for 1–24 h (SAR: 1 W/kg) [ 95 ], although an acute increase in ROS after 20 min of exposure to modulated but not unmodulated 900 MHz RF-EMF was found [ 96 ]. On the other hand, in a mouse neuronal cell line, exposure to a 1.95 GHz RF-EMF (UMTS/3G signal) showed marginal effects on ROS formation and other parameters on its own, but differentially modulated signaling pathways and cytotoxicity when ROS formation was triggered by glutamate or β-amyloid [ 97 , 98 ].…”
Section: Impact Of Emf On the Nervous Systemmentioning
confidence: 99%
“…Similarly, no signs of inflammation, such as more iNOS or NO formation, were found in astrocytes after exposure to 1.8 GHz RF-EMF for 1–24 h (SAR: 1 W/kg) [ 95 ], although an acute increase in ROS after 20 min of exposure to modulated but not unmodulated 900 MHz RF-EMF was found [ 96 ]. On the other hand, in a mouse neuronal cell line, exposure to a 1.95 GHz RF-EMF (UMTS/3G signal) showed marginal effects on ROS formation and other parameters on its own, but differentially modulated signaling pathways and cytotoxicity when ROS formation was triggered by glutamate or β-amyloid [ 97 , 98 ].…”
Section: Impact Of Emf On the Nervous Systemmentioning
confidence: 99%
“…However, we did not detect any induction of cell death or inhibition of clonogenic survival. Lee et al [21] also simultaneously exposed HT22 cells to two types of RF-EMF to evaluate their effects on cell death and beta amyloid treatment (4 W/kg SAR level; CDMA 2 W/kg + WCDMA 2 W/kg for 2 hours). Similarly, no effects were observed on cell proliferation, cell cycle distribution, and cell death as a result of RF-EMF in the absence or presence of Aβ treatment in the cells.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, possible therapeutic beneficial effects were observed on βA-induced oxidative stress when primarycultured rat astrocytes were exposed to RF-EMFs for 24 hours [15]. However, some studies have also shown no changes in the neuronal cells after RF-EMF exposure [1,21].…”
Section: Introductionmentioning
confidence: 99%
“…We used a radial transmission line (RTL) exposure system as an in vitro multifrequency radiation exposure system for this study [ 25 , 26 ]. A typical Code–Division Multiple Access (CDMA) signal at 837 MHz and a Wideband Code–Division Multiple Access (WCDMA) signal at 1950 MHz were applied to the RTL after amplification.…”
Section: Methodsmentioning
confidence: 99%
“…The 100-mm culture dishes were placed at 13.6 cm from the conical antenna, which was located at the center of the exposure chamber, and cells were then exposed to RF-EMF radiation in the culture dishes. This system has already been used in other published cellular studies [ 25 , 26 ]. The variation in RF-EMF exposures on different culture dishes was negligible, when multiple dishes were exposed at the same time: the variation in the average SAR values for WCDMA frequency was ~7.7% of the single dish exposure when three culture dishes were used, and ~2.0% when six dishes were exposed [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%